Politik Hukum Pembentukan Perda Kab. Konawe Selatan No. 14 Tahun 2013 Tentang Retribusi Izin Tempat Penjualan Minuman Beralkohol Perspektif Maqasid Syariah - Anang Maruf; Aris Nur Qadar Ar Razak; Aris Darmawan Al Habib (Institut Agama Islam (IAIN) Kendari, 2022)
Today, the level of alcohol abuse is in an alarming phase. This is inseparable from the massive legality of the circulation of alcoholic beverages. This study aims to determine and analyze the basis, political struggles and reviews of Maqasid sharia in the formation of the Regional Regulation of South Konawe Regency No. 14 of 2013 concerning Levies for permits for selling alcoholic beverages. The type of research used is the type of empirical normative research. Data collection techniques used are interviews, documentation and literature study. Based on the results of research conducted by researchers that the formation of the Regional Regulation of South Konawe Regency Number 14 of 2013 concerning Retribution for Permits for the Sales of Alcoholic Drinks shows that, based on Law Number 12 of 2011 there are three foundations for the formation of legislation, the philosophical basis (Pancasila), sociological (regional state), juridical. In the political struggle that occurred during the discussion of this regional regulation, there was no significant role shown by political parties, especially parties based on Islam, as evidenced by the fact that all political parties approved the regional regulations. in the perspective of maqasid or the purpose of establishing the law is carried out with the principles of maqasid sharia, namely hifz ad-din, hifz an-nafs, hifz, al-ird, hifz al aql, hifz an-nasl, hifz al-mal in this case maqasid sharia is used in order to achieve the common good of the people.